Building a truster environment for e-business : a Malaysian perspective - Din, M.N.; Jamaluddin, M.Z. (Universiti Utara Malaysia, 2002)
Internet identify ‘security’ as a major concern for businesses. In general, the level of security in any network environment is closely linked to the level of trust assigned to a particular individual or organization within that environment. It is the trust element that is crucial in ensuring a secure environment. Besides physical security, security technology needs to be utilised to provide a trusted environment for e-business. Network security components for perimeter defense, i.e., Virtual Private Networks, firewalls and Intrusion Detection Systems, need to be complemented by security components at the applications and user level, e.g., authentication of user. ID or password security solution may be an option but now with the availability of legally binding digital certificates, security in e-business transactions can be further improved. Time and date stamping of e-business transactions are also of concern to prove at a later date that the transactions took place at the stipulated date and time. Digital certificates are part of a Public Key Infrastructure (PKI) scheme, which is an enabling technology for building a trusted epvironment. PIU comprise policies and procedures for establishing a secure method for exchanging information over a network environment. The Digital Signature Act 1997 (DSA 1997) facilitates the PKI implementation in Malaysia. Following the DSA 1997, Certification Authorities (CAs) were set up in Malaysia. This paper describes a trusted platform for spurring ebusiness and provides a Malaysian perspective of it.